Gestão do projeto e sua interface com o canteiro de obras sob a ótica da preparação da execução de obras (PEO) - Arrotéia, Aline Valverde (2013)
During the last twenty years the construction field in Brazil has evolved significantly in response to its market growing and competitiveness. However this evolving path has faced many obstacles such as cultural barriers and the lack of efforts to achieve quality at the Brazilian construction site. As one of the causes of this facts the lack of integration between construction and the designing process generates waste, pathologies, work redone and improvised changes originated by incompatible projects which were taken by incapacitated personnel at an inconvenient moment. At the same time, the great amount of information generated on the designing or construction phases is lost due to the lack of an effective coordination of these activities. From this scenario Souza (2001), has developed two management methods in her doctorate thesis named Preparation for the Execution of Buildings (known as PEO) and the Pro-active Coordination (known as CPA), these methods are based on the application of the processes adopted by the French construction industry on Brazilian construction sites. These methodologies aim to establish the integration of the project phases by a set of actions and activities implemented by a system of meetings where the main objective is to discuss the projects and the planning of the construction site seeking to obtain a better quality and better outcome on the productive process. These methodologies aim to bring expressive improvements on the productivity, as well as on the lowering of waste, on the settlement of goals, on planning actions in accordance with all the agents involved and mainly on the reduction of costs allied to higher quality standards. Thus is an objective of this research to implement the Preparation on the Execution of Buildings (PEO) seeking to understand the management of the designing process and its interface with the construction site. The methodology applied on the development of the analysis is classified as qualitative and it will be carried by the practical application of the research and the evaluation of its results. Thus, the study was divided into two stages, one of them intended for a pilot study of PEO in Company A, and the other to the implementation of PEO on the company B. This way, the method was developed from a system meetings entitled structured in three different stages: the release of PEO; the development of PEO and the completion of the intensive phase of PEO, which were performed over a period from two to three months. The data analysis was structured upon five main aspects which were evaluated during the implementation of the method on the studied companies. These aspects were: the actions taken during the PEO phase, the development of the actions and the participation of the agents; the internal structure of the companies analyzed; The management and design coordination and the contract form of the contractors, architects and engineers. The results obtained demonstrated the PEO method's effectiveness and viability while a booster on the improvement of project management. Therefore, it can be concluded that the PEO is feasible to be applied in building construction companies, since this method can contribute to the integration of the design phases and construction, as well as to the improvement of the communication between the agents involved in the building construction field.